Gaya Kepemimpinan dan Kinerja Pegawai (Studi pada Dinas Sosial Kabupaten Malang) - Ilmi Usrotin Choiriyah (JKMP (Jurnal Kebijakan dan Manajemen Publik), 2015)
The purpose of this research to identify and analyze leadership style is adopted by Social Agency Malang Regency and to know and analyze employee’s performance Social Agency Malang Regency in carrying out their duties. This research used descriptive with qualitative approach. Data collection was done by interview, observation and documentation. Meanwhile, analysis technique used interactive model that consists of data reduction, data presentation, and conclusion. The results showed that the leadership style is adopted by the Head of Social Agency Malang Regency were a democratic leadership style. It can be seen from some aspects of communication, work supervision, direction and decision-making methods that involve the aspirations and participation of employees. The employee performance Social Agency Malang Regency has done well. It is identified by the number of jobs has done well, the quality of the work produced, and the utilization rate of employee time that has been done well fairly in accordance with the specified target.